Living, Narrating and Enhancing the Landscape Through the Ethics of Responsibility - Brugiatelli, Vereno (European Journal of Multidisciplinary Studies, 2022)
This study aims to provide some answers to the following problems regarding the landscape: 1. What does enhancing the landscape mean? 2. Upon which theoretical and operative bases is it possible to intervene in the landscape in order to enhance it? 3. How is it possible to build in a way which promotes good living while respecting the landscape and its environmental equilibrium? I intend to discuss these issues from the perspective of some considerations regarding the narrative of the landscape. Man has always provided accounts about his environment and territory thereby forming a complex idea of the landscape over time. The narrative of the landscape constitutes a sort of collective memory making the landscape a “quasi persona” that interacts with man’s different actions. The basic thesis of this study is to demonstrate that each intervention in the landscape – with the intention of its enhancement and good living – should be inspired by the ethics of responsibility and, thereby, be guided by the narrative of the landscape which conveys its specific and characteristic traits.